Implementation of Government Authority of Semarang City On State Land Tenure (Case Study in Kebonharjo village of Tanjung Mas) - Ahmad Yahya; Gunarto Gunarto (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2019)
The purpose of this study was to: 1). To analyze the implementation of goverment authority Semarang to State land tenure. 2). To analyze the weaknesses of the implementation of goverment authority Semarang to State land tenure. 3). To analyze the solutions of the weaknesses of the implementation of goverment authority Semarang to State land tenure. This research uses empirical research with the sociological approach. Collecting data using primary legal materials and secondary data were collected through observation, interviews and studies of legal documents. Data analysis is done qualitatively, what respondents expressed orally or in writing, and their actual behavior are researched and studied as a part of the whole.Based on the results penelitaan, then obtained some results conclusions; (1). Implementation of Semarang city government authority does not comply with the authority is in this regard is the acquisition of state land that the land is basically controlled by or under control of juridical by PT. KAI and an asset of Ministry of Finance. (2). Weaknesses of implementation of goverment authority Semarang toward mastery of state land that is;First an error in exercising authority and policies implemented by the previous Mayor with the Chief Daop IV Semarang. Both lack of legal certainty over the ownership rights to the land, so that their certificates canceled citizens of the State Administrative Court which considered disabled Semarang administration. Thirdly absence of justice and legal protection against their certificates of citizens, so that between PT. KAI and residents to date on the status of each claim ownership of the land. (3). The solution of the weaknesses that arise in the implementation of goverment authority Semarang toward mastery of state land that is; Semarang city government first sought mediation between citizens and PT. KAI. Both governments Semarang to seek their compensation from PT. KAI to citizens affected. Semarang three governments seeking their relocation and providing temporary shelter for residents.Keywords: Implementation; Government Authority; State Land.